The Science Literacy Capabilities Profile Using Guided Inquiry Learning Models - Haryadi, Rudi; Pujiastuti, Heni (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This research aims to find out the influence of guided inquiry learning models on the ability of scientific literacy in high school students in the city of Tangerang. This research is a pre-experimental design study that aims to determine the ability of scientific literacy by using a guided inquiry learning model for high school students in the city of Tangerang in Newton’s law material. The research design used was One-Group Pretest-Posttest Design with a sample of 32 students of class X MIA 3 of SMAN 11 in Tangerang City. The average N-gain results for students of SMAN 11 Kota Tangerang amounting to 0.4060 are in the medium category. So it was concluded that the ability of scientific literacy by using the guided inquiry learning model of high school students in the Regency and City of Tangerang is in the medium category.